The group-theoretic analysis for d’Alembert’s solutions of the basic equation of exterior ballistics - Lehenkyi, V. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
We consider the basic equation of exterior ballistics and prove that all specializations of the drug function presented by d'Alembert in 1744 transform this equation to some Lie–Sheffers equation. Due to this hidden property, it can be converted to the classical Bernoulli or Riccati equations.